Penghargaan vs Hukuman, Pengukuran Dampak terhadap Kinerja Pegawai - Sudjai; Didit Darmawan (ARBITRASE: Journal of Economics and Accounting, 2022)
The terms of the company's progress must include elements of quality human resources. This is a demand for companies to continue to develop human resources effectively. In the management concept, rewards and punishments aim to improve work behavior and improve employee performance. This study intends to observe the impact of rewards and punishments on employee performance. Research at an expedition company in Surabaya. There are employees on duty in the office and in the field. There are 119 employees. Sampling was done by census. Data collection with the help of a questionnaire. Regression is an analytical tool using SPSS. Rewards and punishments play a significant role in shaping employee performance. The better the reward and punishment policy, the better the employee's performance. These results have implications for management and company leaders to improve work discipline and employee performance